Quality of life in patients with schizophrenia: A 2-year cohort study in primary mental health care in rural China - He, Xiao-Yan; Migliorini, Christine; Huang, Zhuo-Hui; Wang, Fei; Zhou, Rui; Chen, Zi-Lang; Xiao, Yao-Nan; Wang, Qian-Wen; Wang, Shi-Bin; Harvey, Carol; Hou, Cai-Lan (Frontiers in Public Health, 2022)
Objective: Quality of life (QoL) has been always an important way to evaluate the outcomes of schizophrenia, but there have been few previous longitudinal studies and few in middle-income countries. This study aimed to explore the QoL in Chinese patients with schizophrenia treated in primary mental health care and the risk factors of QoL over time. Methods: Patients with schizophrenia treated in primary mental health care in rural/regional areas in Luoding, Guangdong, PR China, were evaluated with an extended questionnaire including the Chinese version of the World Health Organization Quality of Life (WHOQOL-BREF) at baseline and two-year follow-up. Bivariate and multivariate analyses were conducted including Generalized Estimated Equation analyses (GEE). Results: Four hundred and ninety-one patients with schizophrenia in primary care completed the two-year follow up evaluation. The QoL physical, environmental, and social relationships domains showed improvement after the two-year period, but the psychological domain did not. GEE results showed that earlier age of onset, older age, being employed, being unmarried, the thicker waist circumference, less use of clozapine or other SGAs, fewer hospitalizations, more frequent insomnia, more severe depressive and negative symptoms as well as worse treatment insight were independently associated with poor QoL in patients with schizophrenia. Conclusion: According to our results, to improve the quality of life of patients with schizophrenia in primary care, we should pay more attention to the treatment of depression, negative and insomnia symptoms of schizophrenia, the choice and dosage of antipsychotic medication and improvement in the treatment compliance. The combined use of educational and behavioral strategies may improve treatment adherence.